Comparison of intensity‐modulated radiotherapy and forward‐planning dynamic arc therapy techniques for prostate cancer - Metwaly, Mohamed (J Appl Clin Med Phys, 2008)
We compare an inverse‐planning intensity‐modulated radiotherapy (IMRT) technique with three previously published forward‐planning dynamic arc therapy techniques and a newly implemented technique for treatment of prostate only. The three previously published dynamic arc techniques are dynamic arc therapy (DAT), two‐axis dynamic arc therapy (2A‐DAT), and modified dynamic arc therapy (M‐DAT). The newly implemented technique is the bilateral wedged dynamic arc (BW‐DAT). In all dynamic arcs, the multileaf collimator is moving during rotation to fit the prostate, except that, in 2A‐DAT, it is fitting two separate symmetrical rhombi including the prostate. The rectum is shielded during rotation only in the cases of M‐DAT and BW‐DAT. The results obtained indicate that the BW‐DAT, M‐DAT, and DAT techniques provide the intended dose coverage of the prescribed dose to the planning target volume (PTV)—that is, 95% of the PTV is covered by 100% of the dose. The maximum dose to a 3‐cm margin of healthy tissue that surrounds the PTV is lower by 2.5% in the case of IMRT than in both BW‐DAT and M‐DAT, but it is lower by 5.0% than that in both DAT and 2A‐DAT. The maximum dose to the rest of the healthy tissue in the case of BW‐DAT is [Formula: see text]. This dose covers percentage healthy body volumes of [Formula: see text] with IMRT, [Formula: see text] with DAT, and [Formula: see text] with both 2A‐DAT and M‐DAT. Also, this dose is much lower than the accepted maximum dose (52 Gy) to the femoral heads and necks according to Report 62 from the International Commission on Radiation Units and Measurements. Accordingly, it would be possible to neglect delineation of the femoral heads and necks as organs at risk in cases of BW‐DAT. Doses to 15%, 25%, 35%, and 50% ([Formula: see text] , [Formula: see text] , [Formula: see text] , and [Formula: see text]) of the rectum volume in the case of BW‐DAT were [Formula: see text] , [Formula: see text] , [Formula: see text] , and [Formula: see text] respectively. The [Formula: see text] of rectum in the case of IMRT was lower than that in BW‐DAT, M‐DAT, 2A‐DAT, and DAT by 7.3%, 10.3%, 33.0%, and 17.6% of the prescribed dose (78 Gy in 39 fractions) respectively. The [Formula: see text] , [Formula: see text] , and [Formula: see text] of the rectum volume in the cases of IMRT and DAT were comparable (with a maximum variation of 4.5%); they were similarly comparable in the cases of M‐DAT and BW‐DAT (with maximum variation of 1.5%). These same doses in BW‐DAT were lower than those in IMRT by 8.7%, 10.6%, and 6.2% respectively, but they were quite lower than those in 2A‐DAT, because the average variation was 41.6% (with a maximum of 44.0%). The [Formula: see text] , [Formula: see text] , [Formula: see text] , and [Formula: see text] of the bladder volume in the case of BW‐DAT were [Formula: see text] , [Formula: see text] , [Formula: see text] , and [Formula: see text] respectively. The [Formula: see text] and [Formula: see text] of the bladder in the cases of IMRT, M‐DAT, and BW‐DAT were comparable (with a maximum variation of 2.2% and 3.6% respectively), and the mean values of each dose were lower in DAT by 14.3% and 11.7% respectively. However, the values of [Formula: see text] and [Formula: see text] in the four techniques were comparable, with maximum variations of 5.1% and 2.7% respectively. The [Formula: see text] , [Formula: see text] , [Formula: see text] , and [Formula: see text] of the bladder in the case of DAT were lower than those in 2A‐DAT by 20.1%, 26.9%, 16.0%, and 2.7% respectively. Ion chamber measurements showed good agreement between the calculated and measured isocentric doses (maximum deviation: 3.2%). Accuracy of the dose distribution calculation for BW‐DAT was evaluated by film dosimetry using a gamma index, allowing 3% dose variation and 3 mm distance to agreement as the individual acceptance criteria. We found that fewer than 6.5% of the pixels in the dose distributions of the scanned and calculated area of [Formula: see text] cm failed the acceptance criteria. We conclude that, in addition to simplicity of the dose calculation, the BW‐DAT technique provides the intended concave dose distribution for treatment of the prostate only. Compared with IMRT, it produces better dose protection to the most of the rectum volume and to the healthy tissue outside the treatment volume. Also, as compared with the other forward planning dynamic arc techniques, it gives the most favorable isodose distributions to the prostate and rectum. PACS number: 87.53.Tf